JOURNAL OF SETTLEMENTS AND SPATIAL PLANNING SPECIAL ISSUE VOL 3/2014. - ZOTIC, Vasile (Presa Universitară Clujeană, 2015)
Dedicated to the International Conference Rural Space and Local Development with the theme Peripheral Rural Areas between Certain Existence and Uncertain Development